(untitled) (International Journal of Sustainable Development & World Policy, 2020)
The main objective of this paper was empirically examined the trend and its drivers of tax revenue effort in Sub- Saharan African countries using panel data and stochastic frontier analysis techniques inter alia:- random effect, fixed effect, half-normal, exponential-normal, and truncated-normal analysis for a period of 2000 to 2018. The estimation result shows that tax effort is positively and significantly related to openness, Share of agriculture sector, external debt, share of the construction sector, population growth, age dependency, corruption and GDP per capita and negatively and significantly related with a share of the service sector, official development assistance, foreign direct investment, population density, literacy and official exchange rates. In general, depending on the choice of analysis technique, both supply- side factors and demand - side factors are highly affected tax revenue effort and before designing tax policy, therefore, those concerned bodies be going to first determine their tax revenue effort.